Lesbian Identity Negotiation within Conservative Muslim Families: A Dramaturgical Perspective - Amanda Tasya Hendrawati; Rizky Trisna Putri; Ahmad Ridwan (Dinasti Research, 2026)
This study examines the identity experiences of lesbian women within conservative Muslim family environments in Indonesia through the perspective of dramaturgical theory. The research was motivated by the complex social and religious pressures experienced by queer individuals in maintaining personal authenticity while preserving family acceptance. The study aimed to analyze how lesbian women negotiate identity, manage social expectations, and construct adaptive strategies within restrictive religious environments. This research employed a qualitative method with a phenomenological approach. Data were collected through in-depth interviews, digital observation, and documentation studies involving four female university students in Surabaya who had direct experiences in same-sex relationships and were raised in Muslim families with strong religious values. The findings reveal that participants continuously negotiated their identities through front-stage and back-stage performances in everyday life. Religious appearance, behavioral adaptation, and selective openness functioned as strategies for maintaining emotional security and social acceptance within family environments. In addition, safe spaces, supportive friendships, and digital platforms played significant roles in enabling identity expression and emotional resilience. This study contributes to discussions on queer Muslim identity, dramaturgy, religiosity, and social adaptation within contemporary Indonesian society.